2023
DOI: 10.1186/s12868-023-00773-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of eGFP expression in the ChAT-eGFP transgenic mouse brain

Abstract: Background A historically definitive marker for cholinergic neurons is choline acetyltransferase (ChAT), a synthesizing enzyme for acetylcholine, (ACh), which can be found in high concentrations in cholinergic neurons, both in the central and peripheral nervous systems. ChAT, is produced in the body of the neuron, transported to the nerve terminal (where its concentration is highest), and catalyzes the transfer of an acetyl group from the coenzyme acetyl-CoA to choline, yielding ACh. The creati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…Consistent with previous work, we found that the expression of the ACh neuron marker ChAT changes over time or is low in specific brain regions, such as the lateral septum, cerebral cortex, or cerebellum ( Clos et al, 1989 ; Li et al, 2018 ; Gamage et al, 2023 ). Therefore, the well-characterized ChAT-IRES-Cre driver mouse line was used in combination with Cre reporter lines to express tdTomato in ACh neurons to ensure robust soma detection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous work, we found that the expression of the ACh neuron marker ChAT changes over time or is low in specific brain regions, such as the lateral septum, cerebral cortex, or cerebellum ( Clos et al, 1989 ; Li et al, 2018 ; Gamage et al, 2023 ). Therefore, the well-characterized ChAT-IRES-Cre driver mouse line was used in combination with Cre reporter lines to express tdTomato in ACh neurons to ensure robust soma detection.…”
Section: Discussionsupporting
confidence: 92%
“…Firstly, our data provide novel insights into the timeline of when ACh neurons become cholinergic. We report additional or revised ACh neuron populations in the brainstem, the midbrain, and the hypothalamus compared with those previously described in other recent studies ( Li et al, 2018 ; Gamage et al, 2023 ). Secondly, we describe the changes in cholinergic innervation of the cerebellum as well as the cholinergic projections from the habenula to the hindbrain.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The ChAT (BAC) -eGFP mice were created by adding a bacterial artificial chromosome (BAC) clone into the ChAT locus, in which enhanced green fluorescent protein (eGFP) is inserted into exon 3 at the ChAT initiation codon, strongly and selectively express eGFP in all of the CNS and PNS cholinergic neurons, as well as in the non-neuronal cells [ 40 ]. There was almost perfect overlap of both ChAT (BAC) -eGFP and Gt-a-ChAT-labelled neurons in the entire expansion of the BF including the MS, validating the use of the ChAT (BAC) -eGFP transgenic strain or C57BL/6 stain as the age-matched control for this study [ 44 ].…”
Section: Methodsmentioning
confidence: 53%
“…Prior studies using the ChAT promoter to drive transgene expression in transgenic mice have resulted in selective expression in cholinergic neurons. 12 , 13 More recently Martel et al. used a canine adenovirus vector packaging a ChAT-promoter-driven transgene cassette, yielding transduction of ChAT neurons in rat and NHP striatum.…”
Section: Introductionmentioning
confidence: 99%